Juridical Analysis Of Elementary Performed By A Urological Doctor On The Request Of The Court - Prayogo, Dwi; Ahmad Rifai; Aris Prio Agus Santoso (International Journal of Law and Legal Ethics, 2022)
Law No. 17/2016 has emphasized that perpetrators of sexual crimes can be castrated, but this is a polemic for medical personnel who are appointed as executor in this action, because eliminating the patient's normal body functions is very contrary to the duties of a doctor. This study aims to obtain answers to legal protection for urology doctors who perform castration and to find out whether the actions taken by urologists at the request of the court were against medical ethics or not. The approach method used in this research is a library research approach with secondary data collection. The results of further research were analyzed qualitatively. Based on the research that has been done, it can be concluded that the urologist who performs castration at the request of the court, means that the action is an order that must be carried out, but this is contrary to professional standards because castration can have a bad impact on the patient and this is very contrary to professional standards and doctor's code of ethics so that it can be concluded that legal protection cannot be provided because the doctor acts contrary to professional standards and doctor's code of ethics. Castration performed by a urologist is against the code of medical ethics even though it is an order from the court. On the other hand, the doctor does not have the authority to act as a direct executor, while the executor himself is actually a public prosecutor, so that the doctor can refuse the action if it is considered contrary to the code of ethics and conscience.